Implementation of BASEL-II in the Banking Industry (A Case study of Pakistani Banks) - Fiaz Ahmad; Muhammad Abdus Salam (JISR Management and Social Sciences & Economics, 2022)
Banking industry is exposed to different type of risks like credit, operational, interest rate risk, liquidity risk, foreign currency risk, compliance risk, reputational risk, and country risk. Banking industry can only become stable and stronger if they have proper tools to mitigate these risks. Due to product innovation and complexity of operations banks are giving more importance to mitigate these types of risks. Regulators (SBP) are emphasizing banks to develop their tools in order to control these risks. BASEL-II is a basic tool which is used internationally in banking sector to mitigate these risks. Our study is focused on the implementation of BASEL-II in Pakistani Banking Industry. Researcher has analyzed that its implementation will bring positive effect in the Pakistani banking industry. Moreover what are the basic challenges banks are facing during its implementation. Data have been collected from fifteen banks a combination of Large, Medium, Small, Islamic and foreign banks operating in Pakistan selected on random basis. Results are analyzed through Pie Charts. This research will be helpful for the banking professional especially associated with risk management division and working towards the implementation of BASEL-II. Basel-II is still in the phase of implementation in the Banking industry in Pakistan. This research will provide the base to those want to study the after implementation effects of Basel-II in the Banking industry.